028 Treating progressive multiple sclerosis. Issue 6 (24th May 2018) - Hughes, Jordana; Jokubaitis, Vilija; Slee, Mark; Lechner-Scott, Jeannette; Walt, Anneke Van der; Butzkueven, Helmut; Kalincik, Tomas
Abstract : Introduction: We showed that the available immunotherapies do not modify disability outcomes when used in secondary progressive multiple sclerosis. However, these therapies are effective in advanced active multiple sclerosis. Primary progressive multiple sclerosis may present with or without superimposed relapses. Significance of these relapses for disability accumulation and treatment remains contested. We aimed to examine the effect of the available immunotherapies in primary progressive multiple sclerosis. Methods: 1427 eligible patients with primary progressive multiple sclerosis from MSBase were studied. Confirmed disability progression of disability was compared between treated and untreated propensity score-matched cohorts. Multivariable regression models were used to compare disability accrual between primary progressive multiple sclerosis with and without superimposed relapses. Finally, the effect of therapy on disability accrual in cohorts with and without superimposed relapses was analysed. Results: 173 treated and 373 untreated patients were matched. No differences in the risk of disability progression (p=0.79) and improvement (p=0.98) were observed over the median 3 year follow-up. The likelihood of disability progression was relatively lower in patients with superimposed relapses (hazard ratio=0.83, p<0.01). We observed an association between the proportion of time on immunotherapy and the hazard of disability progression in active (hazard ratio=0.96, p=0.01) but not in the inactive primary progressive disease (p=0.21). Conclusion: Superimposed relapses in primary progressive multiple sclerosis represent a favourable prognostic marker, associated with slower disability accrual. This is most likely attributed to the effectiveness of immunotherapy in active primary progressive disease. Relapse activity, therefore, is a treatable modifier of disability accrual in primary progressive disease.